Etude des marges dans les circuits de commercialisation du porc au Cameroun - Tchoumboué, J.; Dia Kamgnia, B.; Ndébi, G. (Tropicultura, 2004)
Study of Marketing Margins in Pig Marketing Channels in Cameroon. In order to provide a better knowledge of the influence of middlemen on livestock and meat prices in Cameroon, pig marketing margins were valued and compared in Yaounde, Douala and Dschang markets between September 1999 and August 2000. The main results showed that the marketing margins generated by the sale of fresh (31.97%) and roasted (31.67%) meats were significantly higher (p< 0.05), compared to pig (27.09%). The mean values of marketing margins in the different markets were higher at Yaounde (53.31%), followed by Douala (46.92%) and lastly by Dschang (33.76%). Transaction costs analysis revealed significant variations (p< 0.05) between Yaounde (115.07 ± 49.74) and the other 2 markets, Douala (51.94 ± 19.48) and Dschang (39.10 ± 18.76), while the mean values of that parameter were 119.01 ± 78.40; 53.16 ± 14.95 and 61.51 ± 21.01 respectively for fresh and roasted meats and pig. However, in linking marketing margins to transaction costs, the study revealed that, while the sale of fresh and roasted meats allows a higher (p< 0.05) trader's profit in Douala and Dschang markets, compared to pig, the profitability for the three products seems to be the same (p> 0.05) in Yaounde market.